Strengthening Job Satisfaction Through Improving Workplace Spirituality And Teacher Professional Competence - Rosdiana Amini; Sunardi Sunardi; Bambang Supriadi (ABM: International Journal of Administration, Business and Management, 2025)
This study explores the influence of workplace spirituality and teacher professional competence on job satisfaction among senior high school teachers in Malang City, Indonesia. In human behavior theory, the research examines how intrinsic values, professional motivation, and relational harmony within the school setting contribute to a teacher's satisfaction. Utilizing a quantitative associative causal approach, the study surveyed 176 respondents using validated instruments and analyzed the data using Partial Least Squares (PLS). The findings reveal that workplace spirituality characterized by meaningful work, sense of community, and value alignment significantly impacts job satisfaction, primarily through the sense of togetherness among teachers. Likewise, teacher professional competence, comprising motives, self-concept, knowledge, and skills, also positively affects job satisfaction, with knowledge as the most dominant contributor. Moreover, the study highlights the mediating role of organizational commitment in strengthening the relationship between workplace factors and job satisfaction. The results emphasize that enhancing workplace spirituality and professional competence can foster a more satisfying and supportive school environment. This research offers theoretical contributions to educational psychology and organizational behavior and provides practical implications for school leaders and policymakers seeking to improve teacher well-being and performance.